Perencanaan Pembelajaran Pendidikan Agama Islam: Sebuah Ikhtiar Penanggulangan Narkoba dan HIV/AIDS bagi Pelajar - Istiqomah Istiqomah (Al-Hayat: Journal of Islamic Education, 2018)
Once of the seriousness abuse drug and HIV/AIDS, the teacher has to refer learning achievement on academic competence is expected to plan the model of learning in drug and HIV/AIDS control. This paper analyzes 1. The concept of PAI learning to plan them; 2. Implementation of PAI learning; and 3. The implications of PAI learning as an effort to defer HIV/AIDS among students. Paper approach with qualitative, descriptive, documentation on credible, dependable, konfirmable, and transferable of phenomenology. It is known that: 1. The concept of learning-based planning improves the various intelligences: a) spiritual; b) emotional and social intelligence; c) intellectual intelligence, and d) kinesthetic intelligence reflected in religious and social values; 2. Implementation of learning model packed with data analyzing model, ethnographic questions, making an ethnographic record; 3. The implications of PAI learning include: Internal factors: self-motivation, heeding the advice of teachers, families milieu, and society and compliance based on the ethical value of learners in religious practice. External factors: supervision, teachers, famillies milieu, community, and synergism of educational institutions with related all programs. The formal indicator is the spiritual collaboration of Imam Suprayogo (holy book, mosque, and ulama), non-drug and HIV / AIDS.Begitu gawatnya penyalahangunaan narkoba dan penularan HIV/AIDS, maka guru selain mengacu produk pencapaian pembelajaran kompetensi akademik diharapkan dapat merencanakan model pembelajarannya dalam penganggulangan narkoda dan HIV/AIDS. Makalah ini menganalisis 1. Konsep perencanaan pembelajaran PAI; 2. Implementasi pembelajaran PAI; dan 3. Implikasi pembelajaran PAIsebagai ikhtiar penanggulanan HIV/AIDS di kalangan pelajar. Penulisan makalah dengan pendekatan deskriptif kualitatif fenomenologi, literasi dokumentatifkredibel, dependabel, konfirmabel, dan transferabel. Diketahui bahwa: 1. Konsep perencanaan pembelajaran berbasis peningkatan berbagai kecerdasan: a) cerdas spiritual; b) cerdas emosional dan sosial; c) cerdas intelektual, dan d) cerdas kinestetis tercermin dalam nilai-nilai agama dan sosial kemasyarakatan; 2. Implementasi model pembelajarannya dikemas dengan model analyzing data, ethnographic questions, making an ethnographic record; 3. Implikasi pembelajaran PAI meliputi: Faktor internal yaitu: motivasi diri, mengindahkan saran guru, milieu—keluarga, dan masyarakat serta kepatuhan berdasarkan nilai etis pemelajar dalam pengamalan agama. Faktor eksternal: pengawasan, guru, milieu--orang tua, masyarakat, dan sinergisme institusi pendidikan dengan lembaga-lembaga terkait. Indikator formal adalah kolaborasi spiritualis Imam Suprayogo (kitab suci, masjid, dan ulama), nir narkoba dan HIV/AIDS.